SIGNIFICANCE OF ECHOGRAPHY IN THE DIAGNOSIS OF ADENOMYOS - Askarova, Zebo; Raximova, Amira (Eurasian Journal of Academic Research, 2024)
In our study, cases of adenomyosis in perimenopausal women with adenomyosis were investigated using the sonographic method. In recent years, the frequency of this disease has increased significantly, often it is applied in the late stages (stages III-IV), which seriously threaten the well-being of patients. This is due to the lack of clear non-invasive criteria for the early stages of adenomyosis.